Improved climate-resilient rice varieties for Colombia - Fedearroz 67 for irrigated rice systems - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Ex-post assessments already indicated its adoption by 31.01% (4,980) of rice growers in Colombia. See OICR #3844.